Gut microbiota-brain interaction: An emerging immunotherapy for traumatic brain injury - Zhang, Yuxuan; Wang, Zhaoyang; Peng, Jianhua; Gerner, Stefan; Yin, Shigang; Jiang, Yong (Experimental Neurology, 2021)
Individuals suffering from traumatic brain injury (TBI) often experience the activation of the immune system, resulting in declines in cognitive and neurological function after brain injury. Despite decades of efforts, approaches for clinically effective treatment are sparse. Evidence on the association between current therapeutic strategies and clinical outcomes after TBI is limited to poorly understood mechanisms. For decades, an increasing number of studies suggest that the gut-brain axis (GBA), a bidirectional communication system between the central nervous system (CNS) and the gastrointestinal tract, plays a critical role in systemic immune response following neurological diseases. In this review, we detail current knowledge of the immune pathologies of GBA after TBI. These processes may provide a new therapeutic target and rehabilitation strategy developed and used in clinical treatment of TBI patients.
CRIS-Team Scopus Importer:2021-01-15
Keywords: CNS; GBA; Immune response; Immunotherapy; TBI